METROSEXUAL MASCULINITY AND POWER RELATIONS IN ROMANTIC CONTEXTS: A STUDY OF STUDENTS AT SEMARANG STATE UNIVERSITY - Nadya Rahma Andjani Putri; Harto Wicaksono (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study aims to determine the views of masculinity from the perspective of metrosexual men and the reasons for choosing to be metrosexual men in the modern era. Metrosexuality is known as a new model of masculinity that describes men who have a high awareness of appearance and lifestyle that is usually closely associated with women. This study uses a qualitative method with Alfred Schutz's phenomenological approach, with data collection techniques through observation, interviews, and documentation, and supported by a literature study in the form of previous journal references relevant to the research topic. The results show that metrosexual masculinity in Semarang State University students is caused by the desire to find a partner and be appreciated by those around them. They like to use skincare and bodycare products, and regularly visit beauty clinics. However, metrosexuality is not a sexual orientation, but rather a lifestyle, behavior, and a person's preferences in terms of appearance and self-care. Changes in metrosexual men are not only limited to physical changes, but also changes in attitudes that reflect power relations. This study provides a deeper understanding of the subjective experiences and meanings that individuals give to the metrosexual phenomenon. Thus, this study can contribute to the understanding of masculinity and lifestyle in the modern era.